Hymns in the Tenni or Slavi language of the Indians of Mackenzie River, in the North-West Territory of Canada [electronic resource]. - Reeve, W. D. (William Day), 1844-1925.; Bompas, William Carpenter, 1834-1906. ([London?] : Society for Promoting Christian Knowledge, 1890)
Text in Slave language. Attributed to Rev. W.D. Reeve or Bishop Bompas--Bibliographies of the languages of the North American Indians / J.C. Pilling. Electronic reproduction. Mode of access: Internet. 44